Administrative Discretion and the Risk of Abuse of Authority in Indonesian Public Administration - Heru Wahyudi; Jaka Maulana; Angga Rosidin (IHSA Institute, 2026)
Administrative discretion is essential in public administration because government officials must often respond to concrete problems, regulatory gaps, urgent situations, and administrative stagnation that cannot be fully addressed through rigid legal rules. In Indonesia, discretionary authority is formally recognized under Law Number 30 of 2014 concerning Government Administration as a lawful mechanism to maintain responsive governmental action. However, discretion also creates a risk of abuse of authority when it is exercised beyond its legal purpose, detached from public interest, or conducted without accountability and adherence to the General Principles of Good Governance. This study aims to analyze the legal position of administrative discretion in Indonesian public administration, examine its potential transformation into abuse of authority, and formulate a balanced legal and governance framework for controlling discretionary power. This research employs normative legal research supported by a conceptual public administration approach through statutory, conceptual, and analytical methods. The study finds that discretion is indispensable for adaptive governance, but its legitimacy depends on clear legal boundaries, transparent reasoning, proper documentation, effective oversight, and a precise distinction between lawful discretion and unlawful misuse of authority. This article concludes that strengthening these safeguards is necessary to support responsive, accountable, and rule-based governance in Indonesia